Neurological outcomes after hematopoietic stem cell transplantation for cerebral X-linked adrenoleukodystrophy, late onset metachromatic leukodystrophy and Hurler syndrome - Saute, Jonas Alex Morales; Souza, Carolina Fischinger Moura de; Poswar, Fabiano de Oliveira; Donis, Karina Carvalho; Campos, Lillian Gonçalves; Deyl, Adriana Vanessa Santini; Burin, Maira Graeff; Vargas, Carmen Regla; Matte, Ursula da Silveira; Giugliani, Roberto; Saraiva-Pereira, Maria Luiza; Vedolin, Leonardo Modesti; Gregianin, Lauro José; Jardim, Laura Bannach (Arquivos de Neuro-Psiquiatria, 2016)
Hematopoietic stem cell transplantation (HSCT) is the only available treatment for the neurological involvement of disorders such as late-onset metachromatic leukodystrophy (MLD), mucopolysaccharidosis type I-Hurler (MPS-IH), and X-linked cerebral adrenoleukodystrophy (CALD). Objective To describe survival and neurological outcomes after HSCT for these disorders.Methods Seven CALD, 2 MLD and 2 MPS-IH patients underwent HSCT between 2007 and 2014. Neurological examinations, magnetic resonance imaging, molecular and biochemical studies were obtained at baseline and repeated when appropriated.Results Favorable outcomes were obtained with 4/5 related and 3/6 unrelated donors. Two patients died from procedure-related complications. Nine transplanted patients were alive after a median of 3.7 years: neurological stabilization was obtained in 5/6 CALD, 1/2 MLD, and one MPS-IH patient. Brain lesions of the MPS-IH patient were reduced four years after HSCT.Conclusion Good outcomes were obtained when HSCT was performed before adulthood, early in the clinical course, and/or from a related donor.
Keywords: hematopoietic stem cell transplantation; leukodystrophy, metachromatic; mucopolysaccharidosis I; adrenoleukodystrophy